2023
DOI: 10.1007/s00392-023-02327-9
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil-to-lymphocyte ratio is associated with cancer therapy-related cardiovascular toxicity in high-risk cancer patients under immune checkpoint inhibitor therapy

Elias Haj-Yehia,
Raluca I. Mincu,
Sebastian Korste
et al.

Abstract: Background Cancer therapy-related cardiovascular toxicity (CTR-CVT) from immune checkpoint inhibitor (ICI) therapy is still incompletely characterized, and patients with pre-existing cardiovascular disease represent a particularly high-risk cohort. Valid parameters for risk stratification of these patients are missing. Neutrophil-to-lymphocyte ratio (NLR) has been shown to predict mortality and adverse events in other cardiovascular cohorts. The present study aims to examine the predictive capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
2
0
0
Order By: Relevance
“…showed a correlation with NLR and the length of hospital stay in myocarditis patients. Previous studies have shown that NLR increased in patients with ICI‐induced myocarditis and that elevated NLR is associated with major adverse cardiovascular events related to ICI therapy 20–22 . Our results further confirm the association between NLR and cardiovascular events as reported in previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…showed a correlation with NLR and the length of hospital stay in myocarditis patients. Previous studies have shown that NLR increased in patients with ICI‐induced myocarditis and that elevated NLR is associated with major adverse cardiovascular events related to ICI therapy 20–22 . Our results further confirm the association between NLR and cardiovascular events as reported in previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that NLR increased in patients with ICI‐induced myocarditis and that elevated NLR is associated with major adverse cardiovascular events related to ICI therapy. 20 , 21 , 22 Our results further confirm the association between NLR and cardiovascular events as reported in previous studies. NLR reflects inflammatory activity, which may be as a possible mediator for severe myocarditis in cancer patients receiving ICIs.…”
Section: Discussionsupporting
confidence: 91%